Effect of different sterilization methods on the quality of red sour soup - RAN Yaoqi, SHI Bin, HE Yangbo, LI Guolin, TIAN Zhuxi, ZHENG Ruzhong, LI Yongfu (Zhongguo niangzao)
To investigate the effects of different sterilization methods on the quality of Guizhou red sour soup, the red sour soup was treated by 3 kinds of different sterilization methods, including ultra high pressure sterilization, pasteurization and steam sterilization, and the effects of different sterilization methods on pH, total acid, total colonies counts, vitamin C, total phenol, 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging rate, nitrite, organic acid, color and odor were determined. The results showed that the sterilization rates of 3 methods were all above 99%, and could slow down the changes of pH and total acid of red sour soup during 100 d of storage. The nitrite contents of all samples was between 1.54-1.96 mg/kg, complying with the national safety standard (<20 mg/kg). At 100 d of storage, the contents of vitamin C, total phenols, DPPH radical scavenging rate, lactic acid, and color difference ΔE value of the red sour soup treated with ultra-high pressure sterilization were 42.94 mg/kg, 348.77 mg/kg, 38.27%-96.08%, 554.63 mg/kg, and 40.69, respectively, which were superior to those treated with pasteurization and steam sterilization. The electronic nose detection results showed that the odor of red sour soup was mainly composed of nitrogen oxides, ethanol and some aromatic compounds. Pasteurization and steam sterilization changed the odor of red sour soup, resulting in the increase of sulfur compounds and alkane compounds. In conclusion, ultra high pressure sterilization was a better sterilization method for red sour soup, which could effectively retain nutrients and flavor.